![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a: \(2A=2^{101}+2^{100}+...+2^2+2\)
\(\Leftrightarrow A=2^{100}-1\)
b: \(3B=3^{101}+3^{100}+...+3^2+3\)
\(\Leftrightarrow2B=3^{100}-1\)
hay \(B=\dfrac{3^{100}-1}{2}\)
c: \(4C=4^{101}+4^{100}+...+4^2+4\)
\(\Leftrightarrow3C=4^{101}-1\)
hay \(C=\dfrac{4^{101}-1}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(A=1+3+3^2+...+3^{99}+3^{100}\)
=> \(3A=3+3^2+3^3+...+3^{100}+3^{101}\)
=> \(3A-A=\left(3+3^2+...+3^{101}\right)-\left(1+3+...+3^{100}\right)\)
<=> \(2A=3^{101}-1\)
=> \(A=\frac{3^{101}-1}{2}\)
b) Ta có: \(B=1+4+4^2+...+4^{100}\)
=> \(4B=4+4^2+4^3+...+4^{101}\)
=> \(4B-B=\left(4+4^2+...+4^{101}\right)-\left(1+4+...+4^{100}\right)\)
<=> \(3B=4^{101}-1\)
=> \(B=\frac{4^{101}-1}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=1+3^1+3^2+3^3+3^4+....+3^{99}+3^{100}\)
\(\Rightarrow3A=3+3^2+2^3+3^4+....+3^{100}+3^{101}\)
\(\Rightarrow3A-A=\left(3+3^2+3^3+...+3^{101}\right)-\left(1+3^1+3^2+....+3^{100}\right)\)
\(\Rightarrow2A=3^{101}-1\)
\(\Rightarrow A=\frac{3^{101}-1}{2}\)
\(A=1+3^1+3^2+...+3^{99}+3^{100}\)
\(3A=3+3^1+3^2+...+3^{99}+3^{100}\)
\(3A-A=\left(3+3^2+3^3+...+3^{100}+3^{101}\right)-\left(1+3^1+3^2+...+3^{100}\right)\)
\(2A=3^{101}-1\)
\(A=\left(3^{101}-1\right):2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(K=2^1-2^2+2^3-2^4+...+2^{99}-2^{100}\)
\(2K=2\left(2^1-2^2+2^3-2^4+...+2^{99}-2^{100}\right)\)
\(2K=2^2-2^3+2^4-2^5+....+2^{100}-2^{101}\)
\(2K+K=\left(2^2-2^3+2^4-2^5+.....+2^{100}-2^{101}\right)+\left(2^1-2^2+2^3-2^4+.....+2^{99}-2^{100}\right)\)\(3K=2-2^{101}\)
\(K=\dfrac{2-2^{101}}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=2+2^2+...+2^{99}+2^{100}\)
\(2A=2^2+2^3+...+2^{101}\)
\(2A-A=\left(2^2+2^3+....+2^{101}\right)-\left(2+2^2+...+2^{100}\right)\)
\(A=2^{101}-2\)
A= 2+2^2+2^3+...+2^99+2^100
=>2A=2^2+2^3+2^4+...+2^100+2^101
=> 2A - A =(2^2+2^3+2^4+...+2^100+2^101)-(2+2^2+2^3+...+2^99+2^100)
=>A = 2^101-2